2017
DOI: 10.1007/s00709-017-1172-2
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide analysis and expression profiling of PP2C clade D under saline and alkali stresses in wild soybean and Arabidopsis

Abstract: Protein phosphatase 2Cs (PP2Cs) belong to the largest protein phosphatase family in plants. Some members have been described as being negative modulators of plant growth and development, as well as responses to hormones and environmental stimuli. However, little is known about the members of PP2C clade D, which may be involved in the regulation of signaling pathways, especially in response to saline and alkali stresses. Here, we identified 13 PP2C orthologs from the wild soybean (Glycine soja) genome. We exami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 57 publications
0
23
0
Order By: Relevance
“…PP2Cs play important roles in various stress signaling pathways. Plant PP2Cs function in response to stresses such as drought, salt, alkali, fungal pathogens (Bhaskara et al, 2012; Chen et al, 2017; Akimoto-Tomiyama et al, 2018) as well as in plant development (Yu et al, 2003; Song et al, 2006; Fuchs et al, 2012; Ren et al, 2018). However, limited research has been conducted on PP2Cs in wheat, and the only report on TaPP2C1 , belonging to group F, is based on its role in resistance to salt stress in transgenic tobacco (Hu W. et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…PP2Cs play important roles in various stress signaling pathways. Plant PP2Cs function in response to stresses such as drought, salt, alkali, fungal pathogens (Bhaskara et al, 2012; Chen et al, 2017; Akimoto-Tomiyama et al, 2018) as well as in plant development (Yu et al, 2003; Song et al, 2006; Fuchs et al, 2012; Ren et al, 2018). However, limited research has been conducted on PP2Cs in wheat, and the only report on TaPP2C1 , belonging to group F, is based on its role in resistance to salt stress in transgenic tobacco (Hu W. et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Two TaPP2C homoeologs in group A were unexpectedly up-regulated by heat treatment but not by drought treatment. A previous study demonstrated that almost all members of group D in soybean ( Glycine max ) and Arabidopsis contain SA responsive element, heat stress responsive element (HSE), and MYB binding site involved in drought-inducibility (MBS) in their promoters (Chen et al, 2017). This finding is consistent with our results that genes in group D responded to pathogen infection as well as heat and drought treatments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The three-dimensional change of water content in drip irrigation leads to the corresponding three-dimensional movement of saline-alkali. In this way, the movement of saline-alkali has its specific law [28]. after infiltration, the unit is ms cm -1 .…”
Section: Saline-alkali Infiltration Of Drip Irrigation Under Sub-soilmentioning
confidence: 99%
“…Also, transgenic studies in maize and Arabidopsis verified that ZmPP2C-A10 function as negative regulator of drought tolerance ( Xiang et al, 2017 ). So far, using bioinformatics analysis, the PP2C gene family has been identified in several species, including Arabidopsis ( Schweighofer et al, 2004 ), rice ( Xue et al, 2008 ), cotton ( Shazadee et al, 2019 ), wheat ( Yu et al, 2019 ), soybean ( Chen et al, 2018 ), and Chinese cabbage ( Khan et al, 2019 ). However, the functional characterization of PP2C genes in cotton remains largely obscure.…”
Section: Introductionmentioning
confidence: 99%